2022
DOI: 10.3390/nu14051072
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Pregnancy Body Mass Index and Risk of Macrosomia and Large for Gestational Age Births with Gestational Diabetes Mellitus as a Mediator: A Prospective Cohort Study in Central China

Abstract: This study aimed to examine the risk of macrosomia and large for gestational age (LGA) births in relation to maternal pre-pregnancy body mass index (BMI) status mediated through gestational diabetes mellitus (GDM). This prospective study included 34,104 singleton pregnancies at 8–14 weeks of gestation. The interesting outcomes were macrosomia (≥4000 g) and LGA (≥90th percentile). Mediation analyses were conducted using log-binomial regression adjusted for age, education, parity, fetal sex, and gestational weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
1
14
0
1
Order By: Relevance
“…An observational study examined the relative impact of a maternal factor on birth weight showed that pre-pregnancy BMI, and gestational weight gain was close with birth weight ( 54 ). A recently published literature found pre-pregnancy overweight or obesity increased the risk of macrosomia and LGA births independently and partly mediated by GDM ( 55 ). Black M H and colleagues conducted a retrospective study of 9,835women and revealed that pre-pregnancy overweight or obesity accounts for 23.3% of LAG in women with GDM and 21.6% in women without GDM ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…An observational study examined the relative impact of a maternal factor on birth weight showed that pre-pregnancy BMI, and gestational weight gain was close with birth weight ( 54 ). A recently published literature found pre-pregnancy overweight or obesity increased the risk of macrosomia and LGA births independently and partly mediated by GDM ( 55 ). Black M H and colleagues conducted a retrospective study of 9,835women and revealed that pre-pregnancy overweight or obesity accounts for 23.3% of LAG in women with GDM and 21.6% in women without GDM ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association between pre-pregnancy BMI value and pregnancy outcomes remains inconclusive in women with PCOS. Additionally, we believe the fact that worse pregnancy outcomes are present in pregestational overweight/obese women, regardless of whether they are diagnosed with PCOS or not [ 22 , 23 , 24 , 25 , 26 ]. Therefore, we thus performed this systematic review and meta-analysis to elucidate the association between pre-pregnancy overweightness/obesity and pregnancy outcomes in the PCOS women.…”
Section: Introductionmentioning
confidence: 99%
“…An increased pre-pregnancy BMI and excessive maternal weight gain in pregnancy have been recognized as prerequisites for fetal macrosomia by many researchers [34][35][36][37]. Even a protective effect of low pre-pregnancy BMI in non-diabetic women has been described [38,39].…”
Section: Discussionmentioning
confidence: 99%